Xylan Is Critical for Proper Bundling and Alignment of Cellulose Microfibrils in Plant Secondary Cell Walls - Crowe, Jacob D.; Hao, Pengchao; Pattathil, Sivakumar; Pan, Henry; Ding, Shi-You; Hodge, David B.; Jensen, Jacob Krüger (Frontiers in Plant Science, 2021)
Plant biomass represents an abundant and increasingly important natural resource and mainly consists of a number of cell types that have undergone extensive secondary cell wall formation. These cell types are abundant in Arabidopsis stems, a well-studied model system for hardwood, the wood of eudicot plants. The main constituents of hardwood are cellulose, lignin and xylan, the latter in the form of glucuronoxylan. The binding of glucuronoxylan to cellulose in the eudicot secondary cell wall represents one of the best-understood molecular interactions within plant cell walls. The evenly spaced acetylation and [4-O-methyl] glucuronic acid substitutions of the xylan polymer backbone facilitates binding in a linear two-fold screw conformation to the hydrophilic side of cellulose and signifies a high level of molecular specificity. However, the wider implications of glucuronoxylan-cellulose interactions for cellulose network formation and secondary cell wall architecture have remained less explored. In this study, we seek to expand our knowledge on this by characterizing the cellulose microfibril organization in three well-characterized glucuronoxylan mutants. The selected mutants display a range of glucuronoxylan deficiency from mild to severe, with findings indicating even the weakest mutant having significant perturbations of the cellulose network, as visualized by both scanning electron and atomic force microscopy. We show by image analysis that microfibril width is increased by as much as three times in the severe mutants compared to the wild type and that the degree of directional dispersion of the fibrils is approximately doubled in all three mutants. Further, we find that these changes correlate with both altered nanomechanical properties of the secondary cell wall, as observed by atomic force microscopy, and with increases in enzymatic hydrolysis. Results from this study indicate the critical role that normal glucuronoxylan composition has on cellulose bundle formation and cellulose organization as a whole within secondary cell walls.